Croisement d’échelles : la famille, la localité et le groupe professionnel - Caroline Mazaud (Temporalités)
This article defends scale variation as being the only methodological and analytical way to grasp a given moment in social trajectories, namely setting oneself up in a craft, observed here thanks to cases in the car industry. The coexistence of diverse professional profiles (between traditional craftsman and entrepreneur) and various modes of access to the status of craftsman (either the classical road to the craft industry or retraining) can be explained by referring to various contexts, i.e. by choosing different focal lengths, tailored to each case. Three cases are studied on three different scales, themselves related to different times : first of all, the domestic dimension, or more precisely conjugal, associated with the life span, then the local context and its community temporality, and finally the global socioeconomic and institutional context attached to the long time history of the professional group.